Upaya Meningkatkan Motivasi Hasil Belajar Siswa Forehand Lob Dan Backhand Lob Melalui Modifikasi Permainan Bulutangkis Di Kelas VIII G SMPN 1 Singojuruh - Utama, Rheynov Alfian; Cipto Nugroho, Rico Armansyah; Prakoso, Bayu Budi; Azkian, Fahmi (Universitas Hamzanwadi, 2024)
This study aims to examine learning activities using game modifications that can increase motivation for learning outcomes in forehand lob and backhand lob material in badminton games. This research method is a type of class action research with the Kemmis and Mc. Taggart model and has 4 phases including planning, taking action, observing and reflecting. The research subjects were 36 students. The data collection instrument is a skill test. All data is quantitative and analyzed descriptively with the % formula. The results of research on learning activities forehand lob cycle I the number of students who completed 12 students (33%), while students who did not complete 24 students (67%). In cycle II, there was a significant increase in the number of students who completed 22 students (61%), while 14 students (39%) were not complete. In the learning activities of the backhand lob cycle I, the number of students who completed 8 students (22%), while 28 students (78%) were not complete. In cycle II, there was a significant increase, namely the number of students who were complete 19 students (53%), while 17 students (47%) were not complete. In conclusion, learning badminton game modifications for two cycles worked well and improved student skills.